2000
DOI: 10.1038/72697
|View full text |Cite
|
Sign up to set email alerts
|

A colorimetric assay for rapid screening of antimicrobial peptides

Abstract: The increased resistance of various bacteria toward available antibiotic drugs has initiated intensive research efforts into identifying new sources of antimicrobial substances. Short antibiotic peptides (10-30 residues) are prevalent in nature as part of the intrinsic defense mechanisms of most organisms and have been proposed as a blueprint for the design of novel antimicrobial agents. Antimicrobial peptides are generally believed to kill bacteria through membrane permeabilization and extensive pore-formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
181
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(189 citation statements)
references
References 19 publications
3
181
0
5
Order By: Relevance
“…When mixed with PDA, lipids tend to form bilayers in interspersed, segregated phases, creating a convenient model system of the lipid bilayer. Kolushiva et al used 3:1:6 PE/PG/PDA and 3:1:6 PE/CL/PDA vesicles to create a simple screening assay to study the interaction of AMPs with the membrane (Kolusheva et al, 2000). Using colorimetric analyses, the insertion of AMPs into the membrane was found to depend on bilayer composition, with higher insertion into the PG-containing system, consistent with observed biological data for levels of antimicrobial activity.…”
Section: Antimicrobial Peptides: Vesiclesmentioning
confidence: 59%
See 1 more Smart Citation
“…When mixed with PDA, lipids tend to form bilayers in interspersed, segregated phases, creating a convenient model system of the lipid bilayer. Kolushiva et al used 3:1:6 PE/PG/PDA and 3:1:6 PE/CL/PDA vesicles to create a simple screening assay to study the interaction of AMPs with the membrane (Kolusheva et al, 2000). Using colorimetric analyses, the insertion of AMPs into the membrane was found to depend on bilayer composition, with higher insertion into the PG-containing system, consistent with observed biological data for levels of antimicrobial activity.…”
Section: Antimicrobial Peptides: Vesiclesmentioning
confidence: 59%
“…Not all lipid systems used as bacterial models reflect the natural composition of a bacterial membrane, yet these models have been used to provide valuable information in regards to the behaviour and influence of AMPs on the membrane. Synthetic polydiacetylene (PDA) has been used in combination with lipids in bacterial membrane mimetics because of its colorimetric properties (Kolusheva et al, 2000). PDA monomers are similar in structure to lipids, and vesicles exhibit colorimetric blue-red transitions when exposed to several environmental perturbations, including changes in surface pressure.…”
Section: Antimicrobial Peptides: Vesiclesmentioning
confidence: 99%
“…The soluble solid content, oil content, acidity, and other physiological properties of various fruits and vegetables have been detected in food industry [10]. Cell viability was tested with a colorimetric method using a reductive coloring reagent such as tetrazoliumsalt, alamarBlue and PrestoBlue in biotechnology [11,12]. Spectrometry can be used in the analysis of pollutants in water and the ocean by measuring the Chemical Oxygen Demand (COD) of organic matter using hydrogen peroxide (H2O2) and potassium permanganate (KMnO4) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Our results have demonstrated that lipid/PDA systems similarly exhibit unique bio-chromatic transitions attributed to specific interfacial perturbation of the incorporated lipid domains. Such interactions indirectly affect the conjugated network of the adjacent PDA framework, thereby inducing colorimetric transitions (2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Such membrane properties have been investigated by a variety of analytical and structural methods (1). To better detect and analyze diverse membrane processes, we have recently developed a novel colorimetric lipid assay (2)(3)(4)(5)(6)(7). This assay has been used to examine various aspects of membrane biology, including enzymatic cleavage of lipids (2), screening of antimicrobial peptides (3), peptide-membrane interactions (4), ion sensing (5), antibody-epitope recognition (6), as well as assessing the activities of membrane penetrationenhancers (7).…”
mentioning
confidence: 99%